The Active Site Of Antithrombin. Release Of The Same Proteolytically Cleaved Form Of The Inhibitor From Complexes With Factor IXa, Factor Xa And Thrombin - Björk, I; Jackson, C M; Jörnvail, H; Lavine, K K; Nordling, K; Salsgiver, W J (Thrombosis and Haemostasis, 1981)
Reactions between near-equimolar amounts of antithrombin and Factors IXa or Xa resulted in the formation of a free, proteolytically modified, two-chain form of the inhibitor, in addition to the inactive anti thrombin-protease complexes. The modified antithrombin produced by either enzyme behaved electrophoretically identical to the previously characterized modified inhibitor formed in the reaction with thrombin. Like in the latter reaction, the formation of the modified antithrombin by Factor Xa was increased in the presence of heparin, while only small amounts were produced by Factor IXa both in the absence and presence of the polysaccharide. Amino-terminal sequence analyses of the isolated modified inhibitor formed by Factor Xa showed that a single Arg-Ser bond in the carboxy-terminal end of the inhibitor had been cleaved. This cleavage site is identical to that previously identified in free thrombin-modified antithrombin. The antithrombin-Factor IXa and antithrombin-Factor Xa complexes were purified and dissociated by ammonia or hydroxyl amine. The dissociation products of both complexes were free enzyme and a modified two-chain form of the inhibitor. Electrophoresis studies and amino-terminal sequence analyses showed that the modified antithrombin obtained from either complex was identical to that produced in free form by the enzymes and also to the modified inhibitor that was shown previously to be released from the antithrombin-thrombin complex. The fact that identical findings were obtained for the reactions between anti thrombin and three enzymes with different specificities strongly supports the previous proposal that the observed cleavage site is the active site of antithrombin.